The structure of pedagogical education in Poland - Monko, Roman (Journal of Education, Health and Sport, 2018)
The article thoroughly reveals the structure and content of pedagogical education in theRepublicofPoland. The types of specialties that train teachers for different types of educational institutions are identified. Plans for preparing teachers are considered. The list of the main documents regulating the system of professional growth and problems of providing teachers ofPolandwith work are presented. The forms of professional development of teachers inPolandhave been identified.